PENGEMBANGAN E-MODUL INTERAKTIF BERBANTUAN UNITY PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL - Alliya Putri Septiani; Linda Herawati; Sri Tirto Madawistama (J-PiMat : Jurnal Pendidikan Matematika, 2026)
This study aims to describe the development process and test the effectiveness of interactive e-modules assisted by Unity on Two Variable Linear Equation System (SPLDV) material. The research method used is Research and Development (R&D) with the Luther-Sutopo development model, which includes six stages, namely concept, design, material collecting, assembly, testing, and distribution. Data were collected through interviews, feasibility questionnaires, response questionnaires, and learning outcome tests. The research instruments involved media and material expert validation sheets to assess technical and content quality, as well as response questionnaires for teachers and ninth-grade students at SMP Negeri 2 Ciamis. The results showed that the Unity-assisted interactive e-module was deemed “Highly Feasible” by media and material experts. The responses from teachers and students showed a very high level of practicality in the learning process. In addition, this e-module proved to be effective in SPLDV material. The final product was distributed in an offline application format that can be accessed via smartphone to support the learning process. Directly, the implementation of this e-module facilitates students' independence and interest in learning mathematics, as well as providing a practical digital teaching media solution for teachers without internet access constraints.Keyword: e-module, luther-sutopo, research and development, SPLDV, Unity